Strategi Hubungan Masyarakat dalam Meningkatkan Citra Perusahaan - Patricia Gaby Pranabella; Durinta Puspasari (Jurnal Syntax Transformation, 2021)
Corporate communication strategies are used to help organizations face the next decade with the strategies and tools that organizations have today. Through Public Relations or public relations the company's communication strategy also helps to follow and be at the forefront of changes that may occur in the future. Because the reputation of the organization is the main factor to decide on a coherent communication strategy. PT. The Central Indonesia Post Office in Surabaya is the object of this research. The Surabaya Central Post Office has created service programs that will change its public perception from negative to positive which will then create a positive reputation in the future. The focus of this research is to understand the PR strategy used by the Surabaya Central Post Office. The theory used in this research is the theory of Strategic Public Relations and reputation to form a positive image. The research method used is descriptive qualitative with case studies that are clearly demarcated through the existing research focus. Data collection was obtained through primary data, namely in-depth interviews and observations, secondary data from literature studies and documentation. The results of this study indicate that the PR of PT. Pos Indonesia Pusat Surabaya has implemented the PENCILS strategy well through Strategy indicators: 1) Publicity, 2) Event (events), 3) News (news), 4) Community (community involvement), 5) Inform (image), 6) Lobby and negotiation, 7) Social responsibility (social responsibility)). Image Indicators 1) Perception, 2) Cognition, 3) Motivation, 4) Attitude.